The effect of different crossing angles to the radar cross section (RCS) of the target in FSR / Abdul Halim Ahmad - Ahmad, Abdul Halim (2014)
This paper presents on the analysis of the effect of different crossing angles to target's radar cross section (RCS) The target used is in this research is a BMW X6 model. The model of car designed using Autodesk 3DS Max and then export to CST Microwave Studio in order to simulate the RCS. The frequencies used for this simulation were based on UHF and VHF. Based on the simulation result, it is shown that the 400MHz of frequency and 90 degree angles of incident plane wave are the best position to define the maximum tracking and more information of RCS can be obtained.